TEXAS; Evaluate, elect and implement a platform independent test framework for automated testing - Andersson, Ludwig; Arnsby, Tobias (My University, 2009)
Under utvecklingen av moduler för mobilt bredband på Ericsson utförs ett omfattande integrering- och verifieringsarbete, för att säkerställa hög kvalitet på produkter som släpps. Fram tills idag sköts majoriteten av verifieringen manuellt. Till följd av en ökad mängd produkter och konfigurationer har arbetsbördan för verifiering ökat. Man har identifierat att många tester är lämpliga att automatisera. Huvuduppgiften för det här projekte har bestått i att utvärderar befintliga testautomatiserings-verktyg, och i slutfasen implementera ett lämligt testautomatiserings- verktyg. För att uppfylla de krav som fanns utvecklades en egen lösning, kallad TEXAS. Med en server-klient-arkitektur OCH pluginhantering har lösningen visat sig vara användbar för att automatisera delar av de testar som utförs på Ericsson. Abstract During the development of mobile broadband modules, Ericsson deals with a number of integration and verification work to ensure high quality is kept when releasing the products. Up until today a large amount of the verification activity is performed by manual testing. Due to an increasing number of products and configurations the workload for the verification team has increased. However, it has been identified that many tests are suitable for automation. The main task of this master thesis work has consisted of evaluating existing test automation tools, and in the end implement a suitable test automation tool. To fulfil the requirements it was decided develop a new test automation tool, called TEXAS. Implemented in a server-client model combined with a plug-in architecture it has proven to be useful to automate a selection of the current tests performed at Ericsson.
Keywords: Datorteknik; Computer Engineering